Influencer Responsibilities in Disseminating Product Information: Consumer Protection Perspective in Indonesia - Nila Muhedina Simarmata; Debora; Lesson Sihotang (Journal of Legal and Cultural Analytics, 2025)
In the digital era, social media has become a primary platform for product marketing, with influencers playing a crucial role in promoting goods and services. However, influencers often promote products that are not registered with the Indonesian Food and Drug Supervisory Agency (BPOM), potentially harming consumers. This study aims to analyze the responsibilities of influencers in promoting unregistered products and the mechanisms of consumer protection available in Indonesia. This research employs a normative legal method by analyzing statutory regulations, including Law Number 8 of 1999 on Consumer Protection and various BPOM regulations. The findings indicate that influencers can be held legally accountable for promoting illegal products, either due to negligence or intentional actions. Furthermore, consumer protection mechanisms are available through BPOM's supervision, sanctions against violators, and legal dispute resolution channels, both in and out of court. Strict law enforcement and comprehensive education are expected to foster a more responsible and safer marketing environment for consumers in the digital era.